THE CONSTRUCTION OF DAKWAH (ISLAMIC MISSIONARY) PHILOSOPHY AND THE POLITICS OF PROSPEROUS JUSTICE PARTY (PKS) OF MAKASSAR: PERSPECTIVE OF FIQH SIYASAH (ISLAMIC POLITICAL LAW) - Karim, Syahrir (Universitas Islam Negeri Alauddin Makassar, 2015)
For PKS, Islamic Law does not only comprise legal-formal laws adopted directly from Islam or absorbed from Islamic values, but also laws non-contradictive to Islam. PKS rests on its ideological construction developed based on the key principles confirming Islam as a complete and perfect concept to deal with all aspects of life. Islam was revealed as guidance for humanity to manage life and living. It is an obligation for every Muslim to establish live order according to the teachings of Islam. Here, Islam is understood as a religion (ad-din), and at the same time a State (ad-daulah), that is, the rules and regulations to manage life in the context of power. From this perspective, PKS pronounce itself as a dakwah (Islamic missionary) party, although, so far, PKS highlights a pragmatic-realistic approach in order to achieve its missionary politics.